PERAN MOTIVASI KERJA DAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT BANK ACEH SYARIAH CABANG BIREUEN - Em Yusuf Iis; Yanita Yanita (Faculty of Economics and Business, Universitas Malikussaleh, 2021)
This study examines the influence of organizational culture on employee performance and examines the mediating effect of work motivation and job satisfaction variables. The research sample was 114 employees at the Aceh Sharia Bank Bireuen Branch. The analytical tool used is path analysis using the SEM method (structural equation modeling) using Amos. The results showed that each variable of organizational culture, work motivation and job satisfaction has a positive and significant effect on performance, and work motivation mediates exogenous variables with endogenous variables partially mediating. Job satisfaction variable, on the other hand, becomes a very good intermediary (full mediation) between exogenous and endogenous variables